The Mechanosensory Role of Primary Cilia in Vascular Hypertension - Surya M. Nauli; Xingjian Jin; Beerend P. Hierck (International Journal of Vascular Medicine)
Local regulation of vascular tone plays an important role in cardiovascular control of blood pressure. Aside from chemical or hormonal regulations, this local homeostasis is highly regulated by fluid-shear stress. It was previously unclear how vascular endothelial cells were able to sense fluid-shear stress. The cellular functions of mechanosensory cilia within vascular system have emerged recently. In particular, hypertension is insidious and remains a continuous problem that evolves during the course of polycystic kidney disease (PKD). The basic and clinical perspectives on primary cilia are discussed with regard to the pathogenesis of hypertension in PKD.